Relationship of psychological contract breach and perceived organizational support with intention to quit- a case study among employees at Sapura Secured Technologies - Abazazilah, Mohd Abbas (2013)
The main purpose of this study is to identify the relationship between psychological contract breach and intentions to quit at among the administration and technical employees Sapura Secured Technologies (SST), Kuala Lumpur. Other objective is to include perceived organizational support to examine the mediating towards the relationships between psychological contract breach and intentions to quit. Data was collected through a questionnaire survey of 200 respondents using the approach of quantitative research methods. Analysis of the quantitative data suggests that there is a relationship between psychological contract breach and intentions to quit among the employees. The results suggested that there is a significant and positive relationship. Besides, this research also examines the relationship of perceived organizational support towards the intentions to quit. The finding showed that there is significant and negative relationship. The longitudinal study is advisable for future research